Factores asociados a caídas en el adulto mayor en el programa de atención domiciliaria - Anaya Moya, Delsi Melina (2018)
Introduction: The objective of the present study was to determine the association between the degree of functional dependence, polypharmacy and degree of comorbidity in older adult falls. Methods: An analytical observational case-control study that included 300 patients in the Home Care Program EsSalud Huánuco was performed. The Sampling method was non-probability convenience sample. Interviews where information on socio-demographic data (age, sex), anthropometric variables (height and weight) risk factors intrinsic falls (polypharmacy, total dependency assessed with the Barthel index, comorbidity evaluated index was obtained was performed Charlson). Results: A total of 300 patients, of which 169 patients had fallen (Table 2), in sociodemographic characteristics predominance of women are representing 64% of the total study population was found is included. No association was found between the variable fall with varying degree of functional dependence (OR = 1.71; p = 0.038), polypharmacy (OR = 2.10; p = 0.0023) and comorbidity (OR = 1.85; p <0.02). He also found no association with the gender variable (OR = 0.64; p = 0.098) and age (OR = 1.26; p = 0.40). Conclusions: This study concludes that the sample size considered and the methodology used, polypharmacy, the degree of dependence and degree of comorbidity are factors associated with falls of the elderly.